The fishes of the islands in the South China Sea - by South China Sea Fisheries Institute, China National Bureau of Aquatic Products (Beijing, China Science Press, 1979)
Text in Chinese
Keywords: South China Sea; Fishes--South China Sea--Identification.; Marine fishes--South China Sea--Identification.